Kinship terms in Croatian and Italian - an example of different articulation of reality - Mardešić, Sandra (Array, 2008)
Starting from the theoretical premises of Sapir-Worf's hypothesis, this paper focuses on the example of kinship terms in Italian and Croatian as an illustrative case of the way in which languages articulate reality differently. The differences and difficulties encountered in the process of translating from one linguistic system into another have been analysed and special emphasis has been given to the problem of polysemy. The analysis of the questionnaire filled by informants has been used to demonstrate the width of changes contemporary Croatian language has undergone influenced by the tendency to simplify the system of kinship terms.